Chemical risk assessment of conventionally and organically grown tomatoes in Côte d'Ivoire - Kouame, Alfred Kohi; Nindjin, Charlemagne; Konan, Georgette Amoin; Bouatenin, Maizan Jean-Paul Koffi; Koussemon, Marina (The North African Journal of Food and Nutrition Research, 2023)
Background: The use of fertilizers in agriculture can be a source of contamination of fruits and vegetables. Aims: This study was to assess the level of contamination of tomatoes by heavy metals (Pb, Cd, Hg, and As), in order to assess the risks of exposure of consumers of tomatoes in Côte d'Ivoire. Material and Methods: More specifically, the assessment focused on the contamination by heavy metals used intensively by producers for the fertilization of vegetable crops. Four heavy metals (mercury, lead, cadmium and arsenic) were tested in tomato samples from both types of agriculture. Results: The average level of mercury in organic tomatoes (0.08290 ± 0.03 mg/kg) and in conventional tomatoes (0.1564 ± 0.1 mg/kg) exceeded the maximum limit (EC N 1881/2006).  However, in organic tomatoes, only mercury level exceeded the required standard, the other heavy metals being present in trace amounts. The content of these other metals in the organic tomatoes exceeded the standard. However, the ratio (hazard quotient) of the weekly heavy metal intake to the provisional tolerable weekly intake for all heavy metals was less than one (1). Conclusion: Consumption of tomatoes from the areas in this study did not pose a health risk to the consumer.Keywords: Organic agriculture, conventional agriculture, heavy metals, dietary exposure.